The Effect of Honeycomb Ribs Polygon Angle of Pla Structure On Bending Strength Produced By 3D Printing Process - Lana Riskiyansyah; Firman Alhaffis; Irwan Kurniawan (International Journal of Science and Environment (IJSE), 2026)
The development of 3D printing technology has increased the use of Honeycomb Rib structures to produce lightweight components with improved mechanical performance. This study aims to analyze the effect of polygon angle variation in Polylactic Acid (PLA) Honeycomb Rib structures on the flexural strength of specimens manufactured using the Fused Deposition Modeling (FDM) process and to determine the optimal polygon angle. The research involved Finite Element Method (FEM) simulation using SolidWorks, followed by specimen fabrication with an FDM 3D printer and three-point bending testing according to ASTM D790. The evaluated parameters included stress distribution, deflection, maximum flexural stress, strain, and flexural modulus. The results show that polygon angle variation affects the mechanical behavior of Honeycomb Rib structures. The 130° polygon angle produced the highest flexural strength with lower deflection than the other variations, resulting in a more uniform stress distribution. These findings provide a reference for developing lightweight structures for automotive applications based on additive manufacturing.